Effect of the golden points and non-golden points on performance parameters in professional padel - Escudero-Tena, A.; Galatti, L.; Sánchez-Alcaraz, B. J.; Muñoz, D.; Ibáñez, S. J. (International Journal of Sports Science & Coaching, 2024)
Since the 2020 season the World Padel Tour (WPT) has incorporated the golden point rule, which consists of playing a point to decide the game when the score is deuce (40-40). The objective of this study was to analyze the characteristics of the golden points and the rest of the points in men's and women's professional padel, as well as to identify the differences between both types of points. A sample of 2752 points (1431 men's and 1321 women's) was used from 394 games identified and finished with a golden point, corresponding to 69 matches played in the 2021 season of the WPT circuit. The variables recorded were the type of point (golden points and non-golden points), player serving, tactical service position, number of net exchanges, effectiveness of the partner serving and effectiveness of the last shot through systematic observation. The results indicate that during the golden points in men's padel, the Australian position is usually used more, while in women's padel the Australian position is more common when the player on the right serves and the traditional one when the player on the left serves. In addition, both in men and women, the most common serves are those directed towards the side wall. On the other hand, except for the errors in women's padel during the golden points, the winning shots are made in areas close to the net and the errors in areas at the back of the court.